2016
DOI: 10.1038/nprot.2016.112
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for imaging axonal transport in aging neurons using the adult Drosophila wing

Abstract: There is growing interest in the link between axonal cargo transport and age-associated neuronal dysfunction. The study of axonal transport in neurons of adult animals requires intravital or ex vivo imaging approaches, which are laborious and expensive in vertebrate models. We describe simple, noninvasive procedures for imaging cargo motility within axons using sensory neurons of the translucent Drosophila wing. A key aspect is a method for mounting the intact fly that allows detailed imaging of transport in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 52 publications
0
64
0
Order By: Relevance
“…The localization of DCF fluorescence in tubular structures inside the wound (Figures 1B,1D,and 1F) suggested that ROS production upon wounding could be occurring in mitochondria. To establish the source of ROS upon wounding, we injected H2DCFDA into embryos expressing mCherry:mito, a mitochondrial marker (Vagnoni and Bullock, 2016). We quantified a significant colocalization between the mitochondrial marker and DCF (maximum correlation coefficient inside the wound of 0.6 ± 0.1; p < 2 3 10 À65 ; Figure 1F and Video S1).…”
Section: Resultsmentioning
confidence: 99%
“…The localization of DCF fluorescence in tubular structures inside the wound (Figures 1B,1D,and 1F) suggested that ROS production upon wounding could be occurring in mitochondria. To establish the source of ROS upon wounding, we injected H2DCFDA into embryos expressing mCherry:mito, a mitochondrial marker (Vagnoni and Bullock, 2016). We quantified a significant colocalization between the mitochondrial marker and DCF (maximum correlation coefficient inside the wound of 0.6 ± 0.1; p < 2 3 10 À65 ; Figure 1F and Video S1).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, how neuronal mitochondria behave in vivo has also required attention. The last decade has seen substantial progress to address this question, based on experimental paradigms that allow monitoring mitochondrial dynamics in vivo in the peripheral and central nervous system of a wide range of species including nematodes (Fatouros et al, 2012; Rawson et al, 2014; Williams et al, 2013), fruit flies (Babic et al, 2015; Pilling et al, 2006; Vagnoni and Bullock, 2016; Wang and Schwarz, 2009a), zebrafish (O’Donnell et al, 2013; Plucinska et al, 2012), and mice (Chandrasekaran et al, 2006; Misgeld et al, 2007). Reassuringly, the basic tenets of mitochondrial dynamics derived from in vitro work have been confirmed in vivo.…”
Section: How (Much) Do Mitochondria Move In Vivo?mentioning
confidence: 99%
“…The ratio of the volume occupied by the nucleus is thus clearly lower than previously reported, and is even smaller for the complete cell if the volume of its dendrites, which are not included, is also considered. An additional important component is provided by mitochondria, only some of which are docked and stationary, and as a result may elsewhere be more polymorphic (Course & Wang, ), In insects, relatively fast changes in mitochondrial position have been demonstrated within the wing nerves of Drosophila (Vagnoni & Bullock, ). This mobility may make it difficult to capture the exact locations of mitochondria using slow conventional methods of fixation.…”
Section: Discussionmentioning
confidence: 99%